Exploring the extent to which simulation-based education addresses contemporary patient safety priorities: A scoping review - Seaton, P.; Levett-Jones, T.; Cant, R.; Cooper, S.; Kelly, Michelle; McKenna, L.; Ng, L.; Bogossian, F. (Elsevier BV, 2018)
Background: There is unprecedented increase in use of simulation-based education in healthcare settings. The key driver is improving quality and safety in healthcare. To date, there is limited understanding of the degree to which this goal has been achieved. Aim: This scoping review aimed to explore the extent to which simulation-based education in healthcare has addressed and impacted contemporary patient safety priorities. Methods: Systematic searches of literature (2007–2016) were based on each of 10 patient safety priorities articulated in Australia's National Safety and Quality Health Service Standards and New Zealand's Health, Quality and Safety Indicators and markers. Included primary studies evaluated transferability to practice and/or behavioural change and improved patient outcomes, based on Kirkpatrick's training evaluation model Level 3 and Level 4. Findings: Fifteen papers met inclusion criteria. Studies aligned with four of ten National Safety and Quality Health Service Standards: (3). Preventing and controlling healthcare associated infections; (4). Medication safety; (6). Clinical handover; (9). Recognising and responding to clinical deterioration. The studies were indicative of potential for simulation-based education to have a significant impact on patient safety. Discussion: Studies that qualify as translational science, demonstrating changes in clinician behaviours and improved patient outcomes, are emerging. Little evidence from Australian and New Zealand contexts suggests that outcomes of simulation-based education in this region are not commensurate with the significant government investments. Conclusion: Translational studies, despite being difficult to design and conduct, should form part of a thematic, sustained and cumulative program of simulation-based research to identify translational science.